Pengaruh E-Commerce terhadap Penjualan UMKM di Kota Palopo - Ariyanti, Zaskia; Arwan, Arwan; Hidayat, Akbar (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of e-commerce on MSME sales in Palopo City. E-commerce has become a key strategy for MSMEs to expand market reach and increase sales effectiveness in the digital era. The research method used was quantitative with a descriptive approach. Data were collected through questionnaires distributed to 30 MSMEs that have adopted e-commerce. Data analysis techniques included descriptive statistical analysis, validity and reliability tests, and simple linear regression analysis. The results show that e-commerce has a positive and significant influence on MSME sales. This is demonstrated by high average scores on e-commerce indicators such as online visibility, user experience, and market reach, as well as increased sales in terms of volume, value, and sales growth. The coefficient of determination (R²) of 0.223 indicates that 22.3% of the variation in sales can be explained by e-commerce adoption. This finding provides evidence that e-commerce can be a strategic solution for MSMEs in increasing their competitiveness and sales.